ALTERNATIVES FOR THE DEVELOPMENT OF THE BULKY FEED MARKET IN UKRAINE - О. Petrychenko; L. Fedoryshyna; O. Kravchuk; I. Petrychenko; O. Korniichuk (Фінансово-кредитна діяльність: проблеми теорії та практики, 2022)
Abstract. The research is devoted to the problem of the ruminant bulky feed market formation in Ukraine in conditions of the world economic integration processes. The dynamics of bulk feed production in Ukraine, supply and demand in the domestic market have been studied. By means of benchmarking price trends in the hay market in Ukraine and England are analyzed. The study found that feeding ruminants will be complete only if all nutrients and biologically active substances are available in the diet in optimal quantities and ratios. Regression analysis proved the direct dependence of cow productivity on production and supply of bulk feed. It is established that Ukraine has favorable natural and economic conditions to meet domestic demand for bulk feed and for the formation of significant export potential. It was found that the integration process of Ukrainian agricultural producers into the world market requires constant analytical study of the sectorial market changes, considering peculiarities of domestic production of bulk feed, highlighting key factors of Ukraine’s presence and potential in the agricultural market of Europe and Asia with account of safety and quality criteria of feed, environmental, social and economic sustainability of feed suppliers. Among the main factors improving the situation on the market of bulky feed are the following: introduction of new technologies for hay and pelleted feed production; creation of feed centers for the industrialized high-quality feed procurement and composing rational mixed diets for various farm animals; development of state programs to support feed production; formation of the legislative basis for the feed industry development; further standardization and certification of its products in accordance with international and European requirements, aimed at promoting integration in the world market and achieving sustainable competitive advantages.